Psychosocial effects of stroke in low-income family context - doi: 10.5020/18061230.2010.p343 - José Nilson Rodrigues de Menezes; Luciana Andrade da Mota; Zélia Maria de Sousa Araújo Santos; Mirna Albuquerque Frota (Universidade de Fortaleza, 2012)
Objective: To understand the psychosocial effects of stroke - cerebrovascular accident (CVA) - in a low-income family context. Methods: A qualitative and descriptive research held in one of the units of Associação Beneficente Cearense de Reabilitação (ABCR) in Fortaleza, Ceará, in the period from June to December, 2002. Six patients with sequel of CVA and their families joined in the study, regardless of age, with an average of six months of physiotherapy. For data collection we applied free observation and semi-structured interviews to patients and families, mediated by specific guiding questions for each group. From content analysis five categories emerged. Results: The difficulties of family life, the feelings of anguish and anxiety prevailed in the quest for rehabilitation, with the treatment being long, requiring determination and awareness of patient-family dyad. The fear of losing their jobs, the responsibility, the expenses and their family life were present in the discourse of patients and relatives, in addition to questions about the disease and concerns about recovery and / or healing. Final considerations: The stroke (CVA) brings as psychological effects feelings of fear, anguish and limitation, contrasting with the determination of the quest for recovery. Socially, the unemployment, both physical and financial dependence and social isolation were highlighted.